PEMANFAATAN KOTORAN AYAM SEBAGAI PUPUK KASCING DI DESA JERUK KECAMATAN LAKARSANTRI SURABAYA - Budiwan, Adi; Syahrial, Ramon; Susanto, Heri (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2024)
The purpose of this activity is also to introduce vermicomposting technology and to familiarize farmers in Jeruk village with the use of vermicomposting fertilizer, who have been using untreated chicken manure. The implementation methods include socialization and training, opinion polls through questionnaires, vermicomposting and organic farming demonstration plots, and focus group discussions. The demonstration plot is a field school for chicken manure managers and farmers, so that participants can understand the entire process of the activity. In order to support the Community Partnership Program (PKM), a program was also carried out in the form of counseling on the use of chicken manure for worm cultivation, the waste of which is vermicomposting which is an organic material that is very good for fertilizer and also for controlling plant diseases. This counseling was followed up with training in worm cultivation and vermicomposting which was attended by farmers. In addition to being given skills, participants were also given media and worm seeds, as well as wooden boxes and pilot units for worm cultivation. Mentoring and coordination were also carried out to facilitate the implementation of worm cultivation, vermicomposting production and its use in environmentally friendly plant cultivation. In addition to being given skills, participants were also given media and worm seeds, as well as wooden boxes and pilot units for worm cultivation. Mentoring and coordination are also carried out to facilitate the implementation of worm cultivation, vermicompost production and its use in environmentally friendly plant cultivation.